SINTESIS BAHAN UBAHAN GRADUAL ALUMINUM TITANAT/KORUNDUM DARI ALUMINA TRANSISI DENGAN PENAMBAHAN MgO - Achmad Sulhan Fauzi; Suminar Pratapa; Mohammad Herman Eko Santoso (Jurnal Matematika Sains dan Teknologi, 2012)
This article describes the results of research on the use of transition alumina for improving the performance of ceramics. Synthesis has been made of gradual changes materials (Functionally Graded Materials, FGM) aluminum titanate (AT) / corundum based on transition alumina powders with the addition of MgO as a stabilizer of AT as much as 2 wt.%. Samples without the addition of MgO was also made for comparison. Transition alumina with and without the addition of MgO were calcined at a temperature of 1100C for 1 hour to become ?-alumina. The powder mixture was compacted at a pressure of 49.3 MPa and then prasintered at a temperature of 1100C for 1 hour, then repeatedly infiltrated with infiltrator TiCl3 solution (20%) which prepared by dissolving the Ti metal powders into HCl. Furthermore, the material sintered at temperatures of 1500C with a holding time for 3 hours. Physical character of materials showed an increase in density and decrease in porosity of the material due to the addition of MgO. Phase identification results obtained from the content of AT and corundum phases which gradual in depth, indicating that FGM has been formed. These results were supported by analysis of x-ray diffraction pattern showing the formation of a solid solution Al2 (1-x) + MgxTi1 xO5 which marked by the shifting of the peak of AT phase in FGM samples with the addition of MgO. Tulisan ini menjelaskan hasil penelitian tentang penggunaan alumina transisi untuk meningkatkan performa keramik. Telah dilakukan sintesis bahan ubahan gradual (Functionally Graded Material, FGM) aluminum titanat (AT)/korundum berbahan dasar serbuk alumina transisi dengan penambahan MgO sebagai penstabil AT sebanyak 2 wt.%. Sampel tanpa tambahan MgO juga dibuat sebagai pembanding. Alumina transisi dengan dan tanpa penambahan MgO dikalsinasi pada temperatur 1100C selama 1 jam sehingga menjadi ?-alumina. Serbuk campuran dikompaksi pada tekanan 49,3 MPa lalu diprasinter pada temperatur 1100C selama 1 jam, kemudian diinfiltrasi secara berulang dengan infiltran larutan TiCl3 (20%) yang dibuat dengan cara melarutkan serbuk logam Ti ke dalam HCl. Selanjutnya bahan disinter pada temperatur 1500C dengan holding time selama 3 jam. Karakterisasi fisik bahan memperlihatkan adanya kenaikan densitas dan penurunan porositas bahan akibat penambahan MgO. Dari hasil identifikasi fasa didapatkan kandungan fasa AT dan korundum yang gradual terhadap kedalaman, menunjukkan bahwa FGM telah terbentuk. Hasil ini didukung dengan analisis pada pola difraksi sinar-x yang memperlihatkan terbentuknya larutan padat Al2(1-x)MgxTi1+xO5 yang ditandai terjadinya pergeseran puncak fasa AT pada sampel FGM dengan penambahan MgO.